Analisis Pengaruh Pendapatan Asli Daerah, Dana Alokasi Umum, dan Dana Alokasi Khusus Terhadap Tingkat Kemiskinan di Sumatera Utara” - Lubis, Putri Kemala Dewi; Sinaga, Hana Ema Nuela; Izza, Salsabillah Nurul; Siahaan, Triana; Simangunsong, Yuni Sari (Jurnal Ilmiah Wahana Pendidikan, 2024)
The chosen research approach involves the description method, utilizing secondary data (time series) gathered from the North Sumatra Central Statistics Agency. To gather information, a documentation and literature study is conducted, adopting a quantitative approach. The analysis employs a multiple linear regression model, executed through the eviews program, to assess the influence of General Allocation Funds, Special Allocation Funds, and Regional Original Income on poverty in North Sumatra. This implies that an increase in general allocation funds is associated with a substantial decrease in the poverty level. On the other hand, Special Allocation Funds demonstrate a positive but insignificant effect on poverty. In essence, an augmentation in special location funds is linked to an increase in the poverty level, albeit not to a significant extent.It is crucial to emphasize that the positive influence of Original Regional Income on poverty underscores a potential challenge in economic development efforts. While an increase in local income may be anticipated, the simultaneous rise in poverty levels necessitates a closer examination of the dynamics at play. This could involve exploring factors such as income distribution, employment opportunities, and the effectiveness of poverty alleviation programs. The inverse relationship observed between General Allocation Funds and poverty suggests that allocating resources through this channel has a tangible impact on reducing poverty. Policymakers and stakeholders could benefit from this insight by considering strategies that optimize the allocation of general funds to address poverty-related issues more effectively. Additionally, the insignificant effect of Special Allocation Funds on poverty warrants a nuanced approach. While their positive influence is acknowledged, the lack of statistical significance necessitates a careful evaluation of the factors contributing to this phenomenon.